Effect of acute ankle experimental pain on lower limb motor control assessed by the modified star excursion balance test - Bertrand-Charette, Michaël; Roy, Jean-Sébastien; Bouyer, Laurent J. (Frontiers in Sports and Active Living, 2023)
Introduction Following most musculoskeletal injuries, motor control is often altered. Acute pain has been identified as a potential contributing factor. However, there is little evidence of this interaction for acute pain following ankle sprains. As pain is generally present following this type of injury, it would be important to study the impact of acute pain on ankle motor control. To do so, a valid and reliable motor control test frequently used in clinical settings should be used. Therefore, the objective of this study was therefore to assess the effect of acute ankle pain on the modified Star Excursion Balance Test reach distance. Methods Using a cross-sectional design, 48 healthy participants completed the modified Star Excursion Balance Test twice (mSEBT1 and mSEBT2). Following the first assessment, they were randomly assigned to one of three experimental groups: Control (no stimulation), Painless (non-nociceptive stimulation) and Painful (nociceptive stimulation). Electrodes were placed on the right lateral malleolus to deliver an electrical stimulation during the second assessment for the Painful and Painless groups. A generalized estimating equations model was used to compare the reach distance between the groups/conditions and assessments. Results Post-hoc test results: anterior (7.06 ± 1.54%; p < 0.0001) and posteromedial (6.53 ± 1.66%; p < 0.001) directions showed a significant reach distance reduction when compared to baseline values only for the Painful group. Regarding the anterior direction, this reduction was larger than the minimal detectable change (5.87%). Conclusion The presence of acute pain during the modified Star Excursion Balance Test can affect performance and thus might interfere with the participant's lower limb motor control. As none of the participants had actual musculoskeletal injury, this suggests that pain and not only musculoskeletal impairments could contribute to the acute alteration in motor control.